# 食物

B Z O J 3028 BZOJ3028

1 1 − x 2 ∗ ( 1 + x ) ∗ 1 − x 3 1 − x ∗ x 1 − x 2 ∗ 1 1 − x 4 1 − x 4 1 − x ∗ ( 1 + x ) ∗ 1 1 − x 3 = x ( 1 − x ) 4 \begin{aligned} &\frac{1}{1-x^2}*(1+x)*\frac{1-x^3}{1-x}*\frac{x}{1-x^2}*\frac{1}{1-x^4}\frac{1-x^4}{1-x}*(1+x)*\frac{1}{1-x^3}\\ =&\frac{x}{(1-x)^4} \end{aligned}

x ( 1 − x ) 4 = x ( 1 + x + x 2 + . . . ) 4 \frac{x}{(1-x)^4}=x(1+x+x^2+...)^4

F ( x ) = ∑ i = 0 ∞ F i ( 0 ) i ! x i \begin{aligned} F(x)=\sum_{i=0}^{\infty}\frac{F^i(0)}{i!}x^i\\ \end{aligned}

( f ∗ g ) ( i ) = ∑ j = 0 i ( i j ) f ( j ) g ( i − j ) (f*g)^{(i)}=\sum_{j=0}^{i}{i\choose j}f^{(j)}g^{(i-j)}

1 n ! ∑ j = 0 n ( n j ) f ( j ) ( 0 ) g ( n − j ) ( 0 ) = n n ! g ( n − 1 ) ( 0 ) = n ( n + 1 ) ( n + 2 ) 6 \begin{aligned} &\frac{1}{n!}\sum_{j=0}^{n}{n\choose j}f^{(j)}(0)g^{(n-j)}(0)&\\ =&\frac{n}{n!}g^{(n-1)}(0)=\frac{n(n+1)(n+2)}{6} \end{aligned}

1 ( 1 − z ) n = ∑ i = 0 ∞ ( n + i − 1 i ) z i \frac{1}{(1-z)^n}=\sum_{i=0}^{\infty}{n+i-1\choose i}z^i

01-20
01-26

08-09 968
03-12 460
11-17 154
07-02 1592